Rancang Bangun Sistem Aplikasi Penjualan Online Berbasis E-Commerce pada UD. Dimsum Madani - Rahmad Fauzi Sanjaya; Junaidi Junaidi; Saiful Amir (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
UD. Dimsum Madani is a culinary-based micro, small, and medium enterprise (MSME) that still relies on a conventional sales system through manual ordering via instant messaging applications, resulting in difficulties in managing incoming orders, error-prone transaction recording, and limited market reach. This study aims to design and build an online sales application system based on e-commerce to help UD. Dimsum Madani market its products more widely and efficiently, make it easier for customers to place orders online, and generate accurate sales reports. The system was developed using the Rapid Application Development (RAD) method, consisting of requirements planning, design workshop, and implementation stages, and was tested using the Black Box Testing method. The results show that the system was successfully built with features including account registration, login, shopping cart, Cash on Delivery (COD) checkout, product management, order status management, and sales reporting, all of which were tested and functioned according to the requirements. The system proved capable of integrating the sales business process, simplifying stock and transaction management, and minimizing the risk of manual recording errors at UD. Dimsum Madani.